Financing of technology-intensive small businesses: Some evidence on the uniqueness of the ICT industry - Ari Hyytinen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2002)
Using recently collected data on Finnish small businesses, we provide evidence that the debt capacity of growth options, defined as the amount of debt that firms optimally raise for an incremental project, is negative, especially in the information and communications technology (ICT) sector. We relate the finding to the R&D projects that small ICT firms pursue. This may explain why the recent ICT `revolution' relied more on equity than on debt. We run a battery of robustness tests, such as estimating robust regressions, addressing reverse causality and developing a sample selection model for the capital structure choice, to illustrate the robustness of our findings. – – Tutkimuksessa analysoidaan pienten ja keskisuurten yritysten kasvuoptioiden velkakapasiteettia yritystason kyselyaineiston avulla. Keskeinen tulos on, että kasvuoptioiden velkakapasiteetti, määriteltynä velan määränä, joka yrityksen on optimaalista ottaa potentiaaliselle kasvuprojektille, on negatiivinen etenkin ICT-sektorilla. Osoitamme, että tämä tulos liittyy pienten ICT-yritysten T&K-toimintaan. Tulos voi selittää sen, miksi viime vuosien voimakas kasvu ICT-sektorilla on tukeutunut enemmän osake- kuin velkarahoitukseen. Tutkimuksen tulosten vahvuutta testataan erilaisilla ekonometrisilla menetelmillä; ne tukevat tutkimuksen keskeisiä tuloksia. – Yritysrahoitus ; pääomarakenne ; ICT ; T&K ; kasvuoptiot
Keywords: E50; G21; G24; G32; 330; Corporate finance; capital structure; ICT; R&D; growth options; Unternehmensfinanzierung; Kapitalstruktur; Informationstechnik; Forschungskosten; Unternehmenswachstum; Klein- und Mittelunternehmen; Finnland